Accelerating bleaching in vitiligo: balancing benefits versus risks. Issue 12 (December 2014) - Seneschal, Julien; Boniface, Katia; Ezzedine, Khaled; Taieb, Alain
Abstract While the goal of available treatment in vitiligo is to regain pigmentation, some patients affected by extensive and treatment‐resistant vitiligo, with a major social and emotional impact, may benefit from depigmentation therapy. However, results from such therapy may not always be satisfactory. So to achieve better, faster and complete bleaching, Webb et al. propose a synergistic approach that combines topical application of bleaching phenols which targets melanocytes and initiate local inflammation with immune adjuvants so as to obtain an enhanced immune response against remaining melanocytes. This strategy could be reliable, but should be evaluated cautiously in future studies, in terms of potential side effects and induction of undesired autoimmunity.